Crowdmapping on the mitigation of sexual harassment - Hasan, Rezwana; Noor, Ramisa Farhat; Noor, Nabiha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022